2017
DOI: 10.1016/j.brat.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychotherapies for posttraumatic stress disorder on sleep disturbances: Results from a randomized clinical trial

Abstract: The effectiveness and mechanisms of psychotherapies for posttraumatic stress disorder (PTSD) in treating sleep problems is of interest. This study compared the effects of a trauma-focused and a non-trauma-focused psychotherapy on sleep, to investigate whether 1) sleep improves with psychotherapy for PTSD; 2) the degree of sleep improvement depends on whether the intervention is trauma or nontrauma-focused; 3) the memory-updating procedure in cognitive therapy for PTSD (CT-PTSD) is associated with sleep improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…Using symptom retention, rather than improvement, as a criterion for examining treatment outcome resulted in a smaller number of symptoms for which PE had a unique effect. The conditional probability of symptom retention in both PE and PCT was highest for difficulty falling asleep (81%), replicating the findings of investigations that have examined additional treatments (e.g., Belleville et al, 2011;Gutner et al, 2013;Larsen et al, 2018;Pruiksma et al, 2016;Woodward et al, 2017;Zayfert & DeViva, 2004). In PE, exposure is used to activate dysfunctional perceptions and beliefs associated with the traumatic event in order to modify emotional processing of the traumatic event (e.g., Foa & Kozak, 1986;Foa et al, 2007).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Using symptom retention, rather than improvement, as a criterion for examining treatment outcome resulted in a smaller number of symptoms for which PE had a unique effect. The conditional probability of symptom retention in both PE and PCT was highest for difficulty falling asleep (81%), replicating the findings of investigations that have examined additional treatments (e.g., Belleville et al, 2011;Gutner et al, 2013;Larsen et al, 2018;Pruiksma et al, 2016;Woodward et al, 2017;Zayfert & DeViva, 2004). In PE, exposure is used to activate dysfunctional perceptions and beliefs associated with the traumatic event in order to modify emotional processing of the traumatic event (e.g., Foa & Kozak, 1986;Foa et al, 2007).…”
Section: Discussionsupporting
confidence: 53%
“…In a more recent study, 44% of patients who had undergone cognitive therapy (that was shown to be highly effective) had difficulty falling or staying asleep after treatment (Woodward et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is assumed that improvements generalize to symptoms at night (i.e. sleep disturbances) and this is supported by initial evidence (Woodward et al, 2017). IRT treatment, on the other hand, mainly addresses night-time symptoms and treatment gains, in turn, were found to generalize to daytime symptoms .…”
Section: The Case Of Ptsd Patientsmentioning
confidence: 93%